INTEGRAL EDUCATION AND LEARNING ASSESSMENT: CONTRIBUTIONS OF HISTORICAL-CRITICAL PEDAGOGY FOR OMNILATERAL HUMAN EDUCATION - de Souza, Fabio Guilherme (Seven Editora, 2025)
In the context of Brazilian education, Comprehensive Education is a proposal capable of expanding human development, overcoming fragmented and restrictive practices. However, learning assessment, often used in a classificatory and exclusionary manner, remains one of the main challenges to its implementation. The objective of this article is to analyze the contributions of Historical-Critical Pedagogy to understanding the interfaces between Comprehensive Education and learning assessment. This is a bibliographical study based on classic and contemporary authors in the field (Saviani, Duarte, Moll, Libâneo, Luckesi, Pimenta), as well as recent data from INEP (2023) and the Center of References in Comprehensive Education (2023). The time frame considered works published between 2008 and 2023, a period of expansion of full-time public policies in Brazil. It is concluded that learning assessment, conceived as a formative and critical practice, constitutes an essential element for the consolidation of Comprehensive Education, ensuring the appropriation of historically produced knowledge and the omnilateral development of individuals. DOI: https://doi.org/10.56238/sevened2025.030-045